Optimal dose and type of exercise to reduce pain, anxiety and increase quality of life in patients with fibromyalgia. A systematic review with meta-analysis - Rodríguez-Almagro, Daniel; Del Moral-García, María; López-Ruiz, María del Carmen; Cortés-Pérez, Irene; Obrero-Gaitán, Esteban; Lomas-Vega, Rafael (Frontiers in Physiology, 2023)
The aim of our meta-analysis was to compile the available evidence to evaluate the effect of physical exercise-based therapy (PEBT) on pain, impact of the disease, quality of life (QoL) and anxiety in patients with fibromyalgia syndrome (FMS), to determine the effect of different modes of PEBT, and the most effective dose of PEBT for improving each outcome. A systematic review and meta-analysis was carried out. The PubMed (MEDLINE), SCOPUS, Web of Science, CINAHL Complete and Physiotherapy Evidence Database (PEDro) databases were searched up to November 2022. Randomized clinical trials (RCTs) comparing the effects of PEBT and other treatments on pain, the impact of the disease, QoL and/or anxiety in patients with FMS were included. The standardized mean difference (SMD) and a 95% CI were estimated for all the outcome measures using random effect models. Three reviewers independently extracted data and assessed the risk of bias using the PEDro scale. Sixty-eight RCTs involving 5474 participants were included. Selection, detection and performance biases were the most identified. In comparison to other therapies, at immediate assessment, PEBT was effective at improving pain (SMD-0.62 [95%CI, -0.78 to -0.51]), the impact of the disease (SMD-0.52 [95%CI, -0.67 to -0.36]), the physical (SMD 0.51 [95%CI, 0.33 to 0.69]) and mental dimensions of QoL (SMD 0.48 [95%CI, 0.29 to 0.67]), and the anxiety (SMD-0.36 [95%CI, -0.49 to -0.25]). The most effective dose of PEBT for reducing pain was 21-40 sessions (SMD-0.83 [95%CI, 1.1 to -0.56]), 3 sessions/week (SMD-0.82, [95%CI, -1.2 to -0.48]) and 61-90 minutes per session (SMD-1.08 [95%CI, -1.55 to -0.62]). The effect of PEBT on pain reduction was maintained up to 12 weeks (SMD-0.74 [95%CI, -1.03 to -0.45]). Among patients with FMS, PEBT (including circuit-based exercises or exercise movement techniques) is effective at reducing pain, the impact of the disease and anxiety as well as increasing QoL.